2014
DOI: 10.1016/j.cell.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A Memory System of Negative Polarity Cues Prevents Replicative Aging

Abstract: Cdc42 is a highly conserved master regulator of cell polarity. Here, we investigated the mechanism by which yeast cells never re-establish polarity at cortical sites (cytokinesis remnants [CRMs]) that have previously supported Cdc42-mediated growth as a paradigm to mechanistically understand how Cdc42-inhibitory polarity cues are established. We revealed a two-step mechanism of loading the Cdc42 antagonist Nba1 into CRMs to mark these compartments as refractory for a second round of Cdc42 activation. Our data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 54 publications
(72 reference statements)
6
83
0
Order By: Relevance
“…A pair of interacting landmark proteins termed Rax1 and Rax2 mark all so-called cytokinesis remnants (Figure 8 b ) (Chen et al 2000), and Rax1/2 anchors a memory complex that blocks budding at such remnants (Meitinger et al 2014). In the absence of Rga1 or the memory complex, cells can bud repeatedly from the same location.…”
Section: Positioning the Polarity Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A pair of interacting landmark proteins termed Rax1 and Rax2 mark all so-called cytokinesis remnants (Figure 8 b ) (Chen et al 2000), and Rax1/2 anchors a memory complex that blocks budding at such remnants (Meitinger et al 2014). In the absence of Rga1 or the memory complex, cells can bud repeatedly from the same location.…”
Section: Positioning the Polarity Sitesmentioning
confidence: 99%
“…In the absence of Rga1 or the memory complex, cells can bud repeatedly from the same location. However, the cytoplasmic channel through the mother-bud neck becomes thinner with each new bud so that eventually the cells cannot successfully complete nuclear division (Meitinger et al 2014). In summary, budding yeast cells inherit prelocalized landmarks that either promote or inhibit subsequent polarization at their locations.…”
Section: Positioning the Polarity Sitesmentioning
confidence: 99%
“…Moreover, when combined with fluorescently-labeled proteins or dyes, researchers can track changes in cell physiology (e.g. organelle structure or function 9,11,32,33 , protein level or localization 12,13,34,35 , promoter activity 8,10,14 , daughter-cell birth characteristics 36,37 ) across the aging process. Importantly, these measures can be associated at single-cell resolution with lifespan or other age-associated changes (e.g.…”
Section: Discoveriesmentioning
confidence: 99%
“…A number of interesting observations have followed. For example, researchers found that delays in nuclear segregation during cytokinesis occur rarely during a cell’s lifetime but increase dramatically in frequency after division speeds slow with age 32 . Researchers also correlated heterogeneity in end-state cell morphology, which had been previously reported by microdissection studies 38,39 , with molecular properties of those cells.…”
Section: Discoveriesmentioning
confidence: 99%
“…Microfluidic devices have been developed to capture yeast cells for high-resolution imaging analysis during vegetative growth (16)(17)(18)(19)(20). Recently, such devices have been designed that enable the tracking of yeast cells throughout their lifespan, making it possible to record and study cellular phenotypic changes during aging (21)(22)(23).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%